Maintaining Traditions in the Midst of the Current Era: Adaptive Strategies of Islamic Boarding Schools to Modernization - Safitri, Eka; Alkhowarizmi, Annas; Luthfi, Rantika; Putri, Najwa Auliya; Fazriani, Eva Tatia (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2025)
Purpose- This study aims to explore how Islamic boarding schools (pesantren) in Indonesia respond to the challenges of modernization, focusing on the balance between preserving traditional values and embracing educational innovation. Design/methods/approach- The research uses a qualitative descriptive approach by examining the philosophical foundation of al-muhafazhah ‘ala al-qadīm as-sālih wa al-akhdz bi al-jadīd al-aslah as a guiding principle for adaptation. Analysis centers on the role of the kiai as a key actor in decision-making and institutional resilience. Findings- The study finds that pesantren have demonstrated remarkable adaptability by integrating modern educational practices while preserving their religious and cultural heritage. The kiai plays a pivotal role in interpreting change, facilitating innovation selectively, and managing tensions between traditionalism and reform. This dynamic allows pesantren to remain relevant without losing their identity. Research Implications- The findings underscore the importance of maintaining a contextual and value-based approach in Islamic education reform. Understanding how pesantren synthesize conservatism with progressivism offers a model for educational institutions facing similar dilemmas in plural and rapidly evolving societies.